Targeted Molecular Therapies in Allergy and Rhinology. (3rd November 2020) - Damask, Cecelia C.; Ryan, Matthew W.; Casale, Thomas B.; Castro, Mario; Franzese, Christine B.; Lee, Stella E.; Levy, Joshua M.; Lin, Sandra Y.; Lio, Peter A.; Peters, Anju T.; Platt, Michael P.; White, Andrew A.
Abstract : Biologic agents, monoclonal antibodies that target highly‐specific molecular pathways of inflammation, are becoming integrated into care pathways for multiple disorders that are relevant in otolaryngology and allergy. These conditions share common inflammatory mechanisms of so‐called Type 2 inflammation with dysregulation of immunoglobulin E production and eosinophil and mast cell degranulation leading to tissue damage. Biologic agents are now available for the treatment of chronic rhinosinusitis with nasal polyps (CRSwNP), asthma, eosinophilic granulomatosis with polyangiitis (EGPA), atopic dermatitis (AD), and chronic spontaneous urticaria (CSU). This paper summarizes the diagnosis and management of these conditions and critically reviews the clinical trial data that has led to regulatory approval of biologic agents for these conditions.